Revealing Tax Non-Compliance Of Msmes From The Perspective Of Local Wisdom Of Madurese Society - Moh Riskiyadi; Nita Selvia Rohmayati; Nurlaily Wulandari (UNIVED Press, 2026)
Micro, small, and medium-sized enterprises (MSMEs) are proliferating; however, this growth is not accompanied by a corresponding increase in tax revenue for these enterprises. Tax non-compliance by MSMEs is a barrier to tax revenue. This study aims to uncover the essence of MSME tax non-compliance from the perspective of the local wisdom of the Madurese community. It seeks to identify the causes and variations of MSME tax non-compliance, drawing on the socio-cultural and local wisdom of the Madurese community. This study uses qualitative methods with a holistic ethnographic approach to uncover the essence of MSME tax non-compliance in Madura. The results indicate that MSME tax non-compliance is caused by Madurese scepticism due to perceived unfair tax benefits and the choice between compliance and non-compliance, driven by differing views on tax law. Various types of tax non-compliance by MSMEs include failing to register as taxpayers, not collecting and paying taxes, and not reporting their tax activities. This study helps to further develop research and provides a basis for tax policymakers to reduce tax non-compliance among MSMEs.